Reconstructing a Damaged Cangkuang Pegon Tafsir: Recovering Local Islamic Intellectual Heritage through Digital Philology in West Java - Abd. Faishol; Muhamad Khabib Imdad; Ahmad Aqiel Azkiya; Mohammad Irfan Farraz Haecal (Center for Research and Development of Religious Literature and Heritage, 2026)
This study examines the Tafsir al-Qur'an Pegon Candi Cangkuang (TAPCC), a seventeenth-to-eighteenth-century Qur'anic commentary manuscript preserved at the Cangkuang Temple Cultural Heritage Site, West Java, Indonesia. Written in Javanese Pegon script, the manuscript contains interlinear Qur'anic interpretations that reflect the vernacular exegetical tradition of early Islamization in the Sundanese region. Extensive material deterioration has rendered numerous Pegon glosses faded, fragmented, or partially illegible, substantially limiting scholarly access to the manuscript's interpretive content. Although previous research addressed the manuscript's historical background and codicological features, no systematic attempt has been made to recover its damaged textual readings through digital philological methods. This study addresses that gap by employing an integrated digital philological-codicological approach combining high-resolution digital imaging, controlled image enhancement, diplomatic transliteration, and contextual philological reconstruction. Analysis focuses on selected folios of the Surah al-Kahf section, which exhibit severe ink deterioration and partial gloss loss. The findings demonstrate that digital image enhancement substantially improves the readability of faded Pegon writing and enables the recovery of several previously inaccessible interlinear readings. The reconstructed glosses reveal a pedagogical tafsir structure grounded in the makna gandhul tradition characteristic of pesantren-based Qur'anic instruction. Codicological evidence further situates the manuscript within seventeenth-to-eighteenth-century Mataram manuscript traditions and illuminates the transmission of Islamic knowledge across Javanese and Sundanese scholarly networks. These findings contribute to the growing scholarship on vernacular Islam, Nusantara manuscript heritage, and the methodological potential of digital philology for recovering damaged Islamic textual traditions in Southeast Asia.